'I never realised everybody felt as happy as I do when I am around autistic people': A thematic analysis of autistic adults' relationships with autistic and neurotypical friends and family. (August 2020) - Crompton, Catherine J; Hallett, Sonny; Ropar, Danielle; Flynn, Emma; Fletcher-Watson, Sue
Many autistic people are motivated to have friends, relationships and close family bonds, despite the clinical characterisation of autism as a condition negatively affecting social interaction. Many first-hand accounts of autistic people describe feelings of comfort and ease specifically with other autistic people. This qualitative research explored and contrasted autistic experiences of spending social time with neurotypical and autistic friends and family. In total, 12 autistic adults (10 females, aged 21–51) completed semi-structured interviews focused on time spent with friends and family; positive and negative aspects of time spent with neurotypical and autistic friends and family; and feelings during and after spending time together. Three themes were identified: cross-neurotype understanding, minority status and belonging. Investigation of these themes reveals the benefits of autistic people creating and maintaining social relationships with other autistic people, in a more systematic way than previous individual reports. They highlight the need for autistic-led social opportunities and indicate benefits of informal peer support for autistic adults. Lay abstract: Although autistic people may struggle to interact with others, many autistic people have said they find interacting with other autistic people more comfortable. To find out whether this was a common experience, we did hour-long interviews with 12 autistic adults. We asked them questions about how it feels when spending time with their friends and family, and whether it felt different depending on whether the friends and family were autistic or neurotypical. We analysed the interviews and found three common themes in what our participants said. First, they found spending with other autistic people easier and more comfortable than spending time with neurotypical people, and felt they were better understood by other autistic people. Second, autistic people often felt they were in a social minority, and in order to spend time with neurotypical friends and family, they had to conform with what the neurotypical people wanted and were used to. Third, autistic people felt like they belonged with other autistic people and that they could be themselves around them. These findings show that having time with autistic friends and family can be very beneficial for autistic people and played an important role in a happy social life.